2016
DOI: 10.1098/rspb.2016.0294
|View full text |Cite
|
Sign up to set email alerts
|

The association between religious homogamy and reproduction

Abstract: Individuals more strongly affiliated to religion have on average more children than less religious ones. Here, based on census data of 3 658 650 women aged 46-60 years from 32 countries provided by IPUMS International and data from the Wisconsin Longitudinal Study (n ¼ 2400 women, aged 53-57 years), we show that religious homogamy is also associated with higher reproduction in terms of a higher number of children and a lower chance of remaining childless. We argue that, together with the relationship between g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
(102 reference statements)
2
12
0
Order By: Relevance
“…For the analysed data, the rates of intermarriage between different religious groups correlated inversely with the size of an individual's religious group in the area of residence. Yet, by building up genetic ties across religious borders via conjoint offspring, religiously heterogamous couples (albeit of lower fertility; Fieder & Huber, 2016) foster social cohesion as family members have genetic ties even if 'separated' by religion. In such newly formed families co-operation will increase according to Hamilton's rules of 'kin selection', whichin a long-term perspectivemay act as a safeguard for social cohesion and peaceful co-existence.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysed data, the rates of intermarriage between different religious groups correlated inversely with the size of an individual's religious group in the area of residence. Yet, by building up genetic ties across religious borders via conjoint offspring, religiously heterogamous couples (albeit of lower fertility; Fieder & Huber, 2016) foster social cohesion as family members have genetic ties even if 'separated' by religion. In such newly formed families co-operation will increase according to Hamilton's rules of 'kin selection', whichin a long-term perspectivemay act as a safeguard for social cohesion and peaceful co-existence.…”
Section: Discussionmentioning
confidence: 99%
“…Only recently, we demonstrated that religious homogamy decreases the chances to remain childless and is also positively associated with a woman's number of children in most but not all analyzed countries, the association strengthening as a woman's education increases (Fieder and Huber, 2016). In that study, where we likewise analyzed worldwide census data together with data form the Wisconsin Longitudinal Study, also educational homogamy was positively associated with number of children.…”
Section: Discussionmentioning
confidence: 92%
“…And yet, alongside this, and in complex relationship with it, has been a strong affirmation of family life both in the New Testament witness (e.g., 1 Timothy 5: 4, 8), and in later Catholic magisterial texts. Contemporary Catholic teaching continues to extol the blessings of a large family (Catechism of the Catholic Church §2373); more generally, the Church has encouraged family life and provided ritual and celebratory forms for families (Fieder and Huber ; Ellis et al. ).…”
Section: Secularization and Fertility Ratesmentioning
confidence: 99%